The Synthesis of Cr/SiO2 Catalyst from a Mixture of Palm Waste Ash - Charcoal and Its Application for the Catalytic Cracking of CPO into Gasoline: Palm waste ash and charcoal based catalyst - Prihatin, Edi; Nazarudin, Nazarudin (Jurnal Bio-Geo Material Dan Energi, 2023)
Due to the increasing reduction in non-renewable natural resources such as petroleum and the increasing amount of ash and charcoal waste from palm oil mills that has not been utilized, the author synthesizes the silica content from a mixture of ash and charcoal from palm oil waste to be used as a Cr/SiO2 catalyst which will be used for cracking. catalytic from CPO (Crude Palm Oil) to gasoline.  This research aims to determine whether a mixture of waste ash and charcoal from the PTP VI Sungai Bahar factory waste can be used as a silica source to produce Cr/SiO2 catalysts and to determine its activity in the catalytic cracking of CPO into gasoline.  The cracking process was carried out in a fixed bed reactor which consists of a horizontal reactor and a vertical reactor and equipped with an electric heater and temperature controller. Catalytic cracking was carried out with several ratios of catalyst : CPO, namely 1:20, 1:25, and 1:30.  Similar cracking process without catalyst (the thermal cracking) was also carried out as a comparison.  The conversion of CHP into gasoline using ratios 1:20, 1:25, 1:30 were 13.67%, 10.78%, 11.59% respectively. Meanwhile, the gasoline conversion produced by thermal cracking was only 9.46%, 9.95%, 6.86%. These results show that catalytic cracking produced more gasoline than thermal  cracking.